FORMULATION DEVELOPMENT AND IN VITRO EVALUATION OF CURCUMIN-LOADED SOLID SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM FOR COLON CARCINOMA - CHENMALA KARTHIKA; RAMAN SURESHKUMAR; AMEER SUHAIL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Cancer is the deadliest disease affecting the life of the people all around the world. Colon cancer is the cancer which is affecting the colon region it is the last part of the gastrointestinal tract which is mainly responsible for the absorption of water and minerals from the food debris. Colon cancer is the second most cancer creating death in the world. It affects both male and female equally. Curcumin is a flavonoid used from decades for the treatment of various ailments including cancer. This present work is to formulate Self-nanoemulsifying drug delivery (SNEDDS) system with the help of curcumin for colon delivery. Materials and Methods: Nanoemulsion was prepared using the curcumin pre-concentrated self-nanoemulsifying drug delivery system, with which tablets were prepared and coated with pectin followed by the evaluation test such as in vitro dissolution and cell line studies. Results: Solubility profile of curcumin was found with a greater impact using Capmul MCM and Labrafac PG which is then added with the surfactants and co-surfactants and were converted into Nano-droplets. F1 formulation was selected after carrying out the characterisation studies and converted into a tablet dosage form and then coated with pectin, in vitro studies depicted a release of 80% in pH 6.8. Conclusions: Formulation of a solid self-Nano emulsifying drug delivery system using curcumin was successfully carried out. From the results obtained, the formulation (F1) was selected for the formation of the tablets and the further experimental part is carried out. The tablet dosage form is then coated with pectin and used for targeting the colon cancer cells for its treatment.